2011
DOI: 10.1002/jmri.22698
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion‐weighted magnetic resonance imaging in the detection of testicular torsion: Feasibility study

Abstract: Purpose: To investigate the feasibility and usefulness of diffusion-weighted magnetic resonance imaging in the detection of testicular torsion. Materials and Methods:Institutional Review Board approval and informed consent from all participants were obtained. Consecutive 28 patients with acute scrotal symptoms were included in this study. Fat-suppressed T2-weighted, dynamic subtraction contrast-enhanced, and diffusion-weighted images were obtained in the coronal plane with a 1.5 T MR unit. An apparent diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 34 publications
(42 reference statements)
0
38
0
1
Order By: Relevance
“…Kangasniemi et al [15] has detected an 18 % and 20 % reduction in the ADC values obtained from mice testicles compared to the control group in 1 st and 2 nd hours respectively . Maki et al [5] have observed a reduction in the ADC values of patients with testis torsion and obtained an 82% accuracy with DWI. Gulum et al [16] have reported reduced ADC values due to the ischemia and the fibrosis in patients with hydrocele.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Kangasniemi et al [15] has detected an 18 % and 20 % reduction in the ADC values obtained from mice testicles compared to the control group in 1 st and 2 nd hours respectively . Maki et al [5] have observed a reduction in the ADC values of patients with testis torsion and obtained an 82% accuracy with DWI. Gulum et al [16] have reported reduced ADC values due to the ischemia and the fibrosis in patients with hydrocele.…”
Section: Discussionmentioning
confidence: 97%
“…However, with the recent advances in functional magnetic resonance imaging (MRI) techniques, varicocele and testicular parenchymal tissue may be evaluated as well [4][5][6]. Diffusion-weighted imaging (DWI) is a functional MRI technique, and is the measurement of the decrease and increase of microscopic water movements within the tissue A reduction of movement of water molecules in tissue is defined as the diffusion restriction [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…We were unable to identify a clear threshold value owing to the small number of subjects. Tsili et al 24 examined 147 healthy testicles with DWI and they stated that reference mean ADC values of testicles were between 1.08 3 10 Maki et al 25 showed that DWI of the testicles with ADC measurement can allow for the detection of TT in patients without any use of contrast media. They used b-factors of 0 and 800 s mm 22 , as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic Resonance (MR) of the testis, by means of classic T1 and T2 weighted sequences, is the second level choice to study the parenchymal pattern, the vascularization and for the morphovolumetric characterization [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%